Construction of Husband and Wife Worker Relationship Patterns Based on the Concept of Gender Equality - Syarif Hidayatullah; Nerisma Eka Putri (JURNAL PENDIDIKAN IPS, 2025)
This study examines the construction of husband-wife relationship patterns based on gender equality concepts, particularly in dual-career families. Traditional family structures have historically placed men in public domains while confining women to domestic responsibilities, creating gender inequality reinforced by patriarchal culture. This library research employs a descriptive-analytic approach to explore how the "mubadalah" concept (reciprocal relationship) can be applied to establish more equitable husband-wife relations. The findings demonstrate that gender differences are sociocultural constructs that contribute to discrimination against women, who often face work–family conflicts in balancing professional and domestic responsibilities. The mubadalah framework, introduced by Faqihuddin Abdul Kodir, emphasizes mutual respect, equality, and justice in relationships. This approach rejects rigid divisions between public and private spheres, advocating equal opportunities and rights for individuals regardless of gender. The study concludes that achieving gender equality requires dismantling patriarchal structures and promoting reciprocal partnerships within families and society. By demonstrating the practical application of the mubadalah concept in modern family dynamics, this study contributes to the broader discourse on gender equality.